2001
DOI: 10.1002/1097-4636(200107)56:1<101::aid-jbm1074>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbodiimide crosslinking conditions on the physical properties of laminated intestinal submucosa

Abstract: Functional tissue engineering of load-bearing repair tissues requires the design and production of biomaterials that provide a remodelable scaffold for host infiltration and tissue regeneration while maintaining the repair function throughout the remodeling process. Layered constructs have been fabricated from chemically and mechanically cleaned porcine intestinal collagen using ethyl-3(3-dimethylamino) propyl carbodiimide (EDC) and an acetone solvent. By varying the concentration of the crosslinker from 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 30 publications
4
68
0
1
Order By: Relevance
“…[45][46][47][48] However, there is a measurable loss of strength that occurs before transfer of mechanical function to the new host tissue. A common approach for increasing the strength of biologic scaffolds composed of ECM or components of ECM (e.g., purified type I collagen) has been the use of chemical crosslinking agents such as CDI, 24,[32][33][34] isocyanate, 49 or glutaraldehyde. [50][51][52] While chemical crosslinking does maintain the mechanical strength of the scaffold, it also necessarily alters the kinetics of degradation and has a deleterious effect on the biologic activity of the degradation products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48] However, there is a measurable loss of strength that occurs before transfer of mechanical function to the new host tissue. A common approach for increasing the strength of biologic scaffolds composed of ECM or components of ECM (e.g., purified type I collagen) has been the use of chemical crosslinking agents such as CDI, 24,[32][33][34] isocyanate, 49 or glutaraldehyde. [50][51][52] While chemical crosslinking does maintain the mechanical strength of the scaffold, it also necessarily alters the kinetics of degradation and has a deleterious effect on the biologic activity of the degradation products.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ECM scaffold degradation as a critical determinant of constructive tissue remodeling becomes even more clinically relevant when considering the widespread use of commercially available ECM materials that have been subjected to chemical and physical methods designed specifically to prevent scaffold degradation and increase the mechanical strength of the materials. 24 A recent study that compares several commercially available ECM scaffold materials has shown that the methods used to process these scaffolds, especially chemical methods to create molecular crosslinks, have marked effects upon host macrophage phenotype surrounding the ECM scaffold and downstream remodeling events. 18 The objective of the present study was to determine the contribution of mononuclear macrophages to the degradation and early remodeling events that follow the implantation of ECM scaffolds for the purpose of tissue reconstruction.…”
mentioning
confidence: 99%
“…Although EDC is an effective cross-linker of collagenous tissues, two constraints associated with crosslinking are excessive surface cross-linking and limitation of cross-linking sites [3]. Higher concentrations of EDC may not correspond to greater bulk cross-linking if surface cross-linking dominates.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the degree of cross-linking increases biodegradation time by making the collagen less susceptible to enzymatic degradation, reduces the antigenicity, increases the tensile strength, and decreases the physical softness of the scaffold. 31,32 Moreover, the ICL matrix can incorporate bioactive substances. The BioSTAR device makes use of this property in that it has a heparin-coated surface.…”
Section: Discussionmentioning
confidence: 99%